Ischemia and no obstructive coronary arteries (INOCA): A narrative review. (December 2022) - Mehta, Puja K.; Huang, Jingwen; Levit, Rebecca D.; Malas, Waddah; Waheed, Nida; Bairey Merz, C. Noel
Abstract: Myocardial ischemia with no obstructive coronary arteries (INOCA) is a chronic coronary syndrome condition that is increasingly being recognized as a substantial contributor to adverse cardiovascular mortality and outcomes, including myocardial infarction and heart failure with preserved ejection fraction (HFpEF). While INOCA occurs in both women and men, women are more likely to have the finding of INOCA and are more adversely impacted by angina, with recurrent hospitalizations and a lower quality of life with this condition. Abnormal epicardial coronary vascular function and coronary microvascular dysfunction (CMD) have been identified in a majority of INOCA patients on invasive coronary function testing. CMD can co-exist with obstructive epicardial coronary artery disease (CAD), diffuse non-obstructive epicardial CAD, and with coronary vasospasm. Epicardial vasospasm can also occur with normal coronary arteries that have no atherosclerotic plaque on intravascular imaging. While all predisposing factors are not clearly understood, cardiometabolic risk factors, and endothelium dependent and independent mechanisms that increase oxidative stress and inflammation are associated with microvascular injury, CMD and INOCA. Cardiac autonomic dysfunction has also been implicated in abnormal vasoreactivity and persistent symptoms. INOCA is under-recognized and under-diagnosed, partly due to the heterogenous patient populations and mechanisms. However, diagnostic testing methods are available to guide INOCA management. Treatment of INOCA is evolving, and focuses on cardiac risk factor control, improving ischemia, reducing atherosclerosis progression, and improving angina and quality of life. This review focuses on INOCA, relations to HFpEF, available diagnostics, current and investigational therapeutic strategies, and knowledge gaps in this condition. Graphical abstract: Image 1 Highlights: INOCA is associated with adverse cardiovascular mortality and outcomes, including myocardial infarction and heart failure. INOCA portends an adverse prognosis in both sexes. Women are more impacted by angina, recurrent hospitalizations, and a lower quality of life. In addition to diffuse atherosclerosis and endothelial dysfunction, CMD is implicated in INOCA. Vasospasm can also occur without visible plaque. Invasive coronary function testing assesses abnormal epicardial and microcirculatory dysfunction as well as vasospasm. Treatment includes anti-anginal/anti-ischemic and non-pharmacologic strategies, while outcomes-based trials are ongoing.